The Concept of Rights and Protection to Employees: A Comparative Overview - Abd Hamid Abd Murad (IJIT, Universiti Kebangsaan Malaysia, 2024)
Issues relating to the rights and protection accorded to employees throughout their employment with the employers is a matter that has been given much attention and treated with utmost priority in any organization, be it in the public or the private sector. It is an undeniable fact that the success story of any organization in the generation of profits in its enterprise or the smooth running in achieving the organization's desired objectives is much attributed to having a reliable, skilled and efficient workforce. Today, employees have been regarded as one of the most valuable assets of any organization. In pursuant thereto, apart from having various employment packages, laws regulating employment were enacted as protective measures in guiding both employers and employees. At the international level, rights and protections to employees have been embedded in the Universal Declaration of Human Rights. Comparatively, under the Shariah, though a similar concept has been forwarded, the notion of employment has been elevated to the status of ‘ibadah. Islam places importance of adhering to the Shari`ah principles in dealing with protection accorded to employees. As employment is regarded as ‘ibadah’ the employees are required and enjoined to observe full dedication, sincerity and commitment to their tasks. It is the responsibility of the employers, on the other hand, to ensure that the welfare of their employees is well protected. This paper attempts to outline the concept of employment under the Shari’ah and civil perspectives and to provide a comparative understanding on the rights and protection accorded to employees.